PEMANFAATAN TEKNOLOGI INFORMASI DALAM PENEGAKAN DISIPLIN PEGAWAI NEGERI SIPIL PADA MASA PANDEMI COVID-19 - Rochmat Ali Syaefudin (Journal Publicuho, 2020)
Merit principle on implementing the management of the state civil apparatus needs to be applied, including the use of information technology. The use of information technology in public services by government agencies has increased during the corona virus (COVID-19) pandemic. The process of enforcing the civil servants discipline regulation of requires adaptation during the COVID-19 pandemic. The discipline of state civil servants in Indonesia is regulated through Government Regulation Number 53 of 2010 concerning civil servant discipline which is designed to be implemented in normal, not pandemic, conditions. The Head of The National Civil Service Agency issued Circular Letter Number 12/SE/IV/2020 as a guideline for the implementation of summons, examinations, and submission of decisions on imposing disciplinary sentences for civil servants during the COVID-19 pandemic. Information technology has been utilized in efforts to enforce discipline during the COVID-19 pandemic by using electronic mail (e-mail), instant messaging applications, and / or teleconferencing. Complete and up-to-date data is indispensable for electronic discipline. Using digital signatures can save time, money and speed up the process of resolving disciplinary offenses.